Entyposis cordipenis new species from Ethiopia (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini) - Sehnal, Richard (Zootaxa, 2017)
Entyposis Kolbe, 1895 (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini) was established for Schizonycha cavicollis Fairmaire, 1887 and newly described Entyposis impressa Kolbe, 1895. Lacroix & Montreuil (2012) revised the genus, designated S. cavicollis Fairmaire, 1887 as the type species and described six new species: Entyposis bidentata, E. martinezi, E. rasplusi, and E. madogolelei from Mozambique; E. excavata from Tanzania; and E. squamulata from Kenya and Tanzania. They also synonymized E. nyukana (Kolbe, 1910) and E. montana (Moser, 1913) with E. mendax Péringuey, 1904. Entyposis differs from other schizonychine genera in having a low occipital carina and with the pronotum in both sexes thickened basally into conspicuous bulges (with medial tubercle) and with deeper medial impression extending anteriorly into a weak or prominent point (Kolbe 1895; Lacroix & Montreuil 2012). Entyposis is very similar to Entypophana Moser, 1913. Both genera are characterized by conspicuous bulges (with lateral tubercle) on the pronotum, but Entypophana differs by having a double vertical frontal carina and occipital carina medially elevated into a simple or double horn or a broad, straight edge. The pronotum of both genera is laterally thickened into conspicuous bulges (with lateral tubercle) and medially bears a shallow, apically narrowing impression (Burgeon 1946; Moser 1913, 1917; Sehnal 2017).